Testing the theory of planned behavior to predict used battery disposal intentions among university students - Chainarong Apinhapath (Mahidol University. Mahidol University Library and Knowledge Center, 2023)
Toxic metals are used in batteries which end up in landfill sites and which may reach humans via the food chain and food web. Proper disposal of used batteries is needed. However, the factors related to proper disposal need to be better understood. This study aims to examine the theory of planned behavior (TPB) and its potential for predicting the behavioral intention for proper disposal of used batteries among students at Thammasat University, Rangsit campus. Survey research was conducted by questionnaire. The students responded about their intentions, attitudes, subjective norms (SN), perceived behavioral control (PBC), beliefs, exposure to information, existing waste bins, demographic data, and battery use data. The results revealed that SN, PBC, attitude, and exposure to information are predictors of intention to dispose of used batteries in specific waste bins. Therefore, specific waste bins should be employed to encourage proper disposal of used batteries.